E-HRM SYSTEM AT THE FISH BREEDING RESEARCH CENTER (BRPI) SUKAMANDI USING WATERFALL METHOD - Ramdhani, Eka Chandra; Nuraini, Intan Anilia; Asep, Asep; Sapitri, Juniarti Eka; Natalia, Fransisca (Journal of Information System, Informatics and Computing, 2023)
This research discusses the theme of developing an information system for human resource management (HR) at the Sukamandi Fish Breeding Research center(BRPI). Some processes at BRPI are still carried out in common ways, such as applying for leave, transferring employees, pension information, and preparing reports. This condition results in problems that arise, such as delays in managing and processing employee information and data by Civil Service Staff. This is designing an e-HRM (electronic-Human Resource Management) information system that can produce accurate information in a short time, as well as providing a reference basis for agencies in overcoming existing problems. The research method used is the waterfall development model which begins with analyzing user needs based on the actors involved, designing tailored to user needs, implementation, verification and the final stage of maintenance. The discussion in this research includes employee data management, such as employee transfers, leave requests, pension information, and making reports at BRPI Sukamandi. The result of this research is to design and build an information system for BRPI Sukamandi that makes it easier for Civil Service staff to organize, process and maintain data about personnel (employees) and then increase the productivity of each employee.